CULTURAL TRANSMUTATIONS: MIGRATION AND IDENTITY IN THE WHITE MASAI - S., Lekshmi.; Viswanath, Harsha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Adapting to a new environment is a gradual process, with the pace of transition differing for each individual. The autobiographical novel ‘The White Masai’ tells the story of a German woman whose life undergoes a dramatic transformation after she meets and migrates to be with her "Masai warrior." Through her narrative, Corinne explores both Western and Masai cultures, highlighting the gender inequalities prevalent among the Masai tribes and the identity crises she experiences. The Masai people maintain their ancient rituals, customs, and simple lifestyle. This paper primarily projects the harsh realities of Masai tribes, their culture and the displacement trauma experienced by the author.